CAUSES OF ADVERSE FETAL AND NEONATAL OUTCOMES IN PATIENTS WITH SEVERE PREECLAMPSIA AND /OR HYPOTROPHIC FETAL DISTRESS - Елена Станиславовна Кравцова; Снежана Игоревна Бурякова; Ольга Александровна Бельницкая; Оксана Николаевна Фильчакова (The Publishing House Medicine and Enlightenment, 2020)
Aim - to determine the causes of unfavorable outcomes for fetuses and newborns in patients with severe preeclampsia and/or hypotrophic fetal distress. Materials and methods: in a level III hospital, a retrospective analysis of the clinical characteristics and results of ultrasound studies in 444 patients who gave birth before 34 weeks of pregnancy was carried out. Three comparison groups were formed depending on the clinical and paraclinical assessment of the course of pregnancies. Results. The analysis of the somatic status, clinical course of pregnancy, childbirth, assessment of the state of newborns and placental morphohistological examination. Conclusions. Unfavorable outcomes for fetuses and newborns with delivery up to 34 weeks for severe preeclampsia and hypotrophic fetal distress occurred in 63.8 % of cases, hypotrophic fetal distress - in 46.8 % of cases, preeclampsia - in 27.3 % of cases.